The Problems and Countermeasures of Chongqing's University Think Tanks Participating in Government Decision-Making - Guo, Peiyao (Transactions on Economics, Business and Management Research, 2024)
Chongqing has abundant talent and academic resources, and has a solid foundation for building university think tanks. There are problems with the decision-making and consulting abilities of researchers, poor communication between the government and university think tanks, and low efficiency in converting theoretical output into practical application in Chongqing's university think tanks. Therefore, the service of think tanks to government decision-making is still insufficient, and the efficiency of adopting or forming policies for think tank results is not high, resulting in insufficient decision support. In this regard, it is recommended to create a flexible and scientific talent management approach, facilitate information communication channels between the government and universities, and accelerate the process of transforming theoretical achievements into practical applications